Genetic determinants of cardiometabolic risk factors in rural families in Brazil. Issue 5 (19th February 2016) - Pena, Geórgia G.; Martinez‐Perez, Angel; Dutra, Míriam Santos; Gazzinelli, Andrea; Corrêa‐Oliveira, Rodrigo; Soria, José M.; Velasquez‐Melendez, Gustavo
Abstract : Objectives: The purpose of this study was to estimate the heritability of genetic and environmental correlations between cardiometabolic risk factors in extended pedigrees. Methods: The Jequitinhonha Community Family Study Cohort (JCFSC) consists of individuals aged ≥18 years living in rural villages. Family pedigrees were constructed of the cohort. The following data were collected: demographic and socioeconomic status, lifestyle variables, anthropometrics, and lipid traits. Results: The JCFSC consists of 931 individuals distributed into 69 pedigrees with 4, 907 members in total. The heritabilities were 0.47 for total cholesterol (TC), 0.44 for triglycerides (TG) and 0.42 for high‐density lipoprotein cholesterol (HDLc), 0.49 for metabolic syndrome, approximately 0.60 for anthropometric traits and 0.30 for blood pressure/hypertension. Significant genetic correlations ( ρ g ) were found mainly between TG and TC ( ρ g = 0.58) and hypertension and TG ( ρ g = 0.52). Systolic blood pressure (SBP) was correlated with TG ( ρ g = 0.39) and HDLc ( ρ g = −0.30). Diastolic blood pressures correlated with TG ( ρ g =0.56) and TC ( ρ g =0.30). Genetic correlations were also found between anthropometric traits, including: body mass index (BMI) and TG ( ρ g =0.34), waist circumference (WC) and TG ( ρ g =0.42), and WC and HDLc ( ρ g =‐0.33). Household effects were found for HDLc ( c 2 = 0.19), SBP ( c 2 = 0.14) and Hypertension ( c 2 = 0.14). Conclusions: To some phenotypes, including lipids, hypertension, blood pressure, and anthropometric traits, genetic contribution is important in the determination of cardiometabolic risk factors. This study provides a foundation for future studies. These will mainly focus on rare variants that could describe the genetic mechanisms influencing cardiometabolic risk. Am. J. Hum. Biol. 28:619–626, 2016. © 2016 Wiley Periodicals, Inc.